High Speed Experimental Study of Friction Induced Vibration in Disc Brakes - Hassan, Muhammad Zahir; Magaswaran, K.; Phuman Singh, A.S. (Trans Tech Publications Inc, 2012)
Brake dynamic groan noise which is a low frequency phenomena associated with brake stop condition or slow brake release. This phenomenon said to be a friction-speed characteristic and commonly associated with low speed events. Thus a high speed test regarding this phenomenon is done. In conjunction with speed, pressure relation is also tested. Analysis of groan occurrence in relation of the speed and pressure is performed. The pressure relation to this event is expected to widen the study of this phenomenon which currently confined to stick and slip motions.